Influence of Irradiance, Flow Rate, Reactor Geometry, and Photopromoter Concentration in Mineralization Kinetics of Methane in Air and in Aqueous Solutions by Photocatalytic Membranes Immobilizing Titanium Dioxide - Ignazio Renato Bellobono; Mauro Rossi; Andrea Testino; Franca Morazzoni; Riccardo Bianchi; Giulia de Martini; Paola Maria Tozzi; Rodica Stanescu; Cristina Costache; Liliana Bobirica; Mauro Luigi Bonardi; Flavia Groppi (International Journal of Photoenergy)
Photomineralization of methane in air (10.0–1000 ppm (mass/volume) of C) at 100% relative humidity (dioxygen as oxygen donor) was systematically studied at 318±3 K in an annular laboratory-scale reactor by photocatalytic membranes immobilizing titanium dioxide as a function of substrate concentration, absorbed power per unit length of membrane, reactor geometry, and concentration of a proprietary vanadium alkoxide as photopromoter. Kinetics of both substrate disappearance, to yield intermediates, and total organic carbon (TOC) disappearance, to yield carbon dioxide, were followed. At a fixed value of irradiance (0.30 W⋅cm-1), the mineralization experiments in gaseous phase were repeated as a function of flow rate (4–400 m3⋅h−1). Moreover, at a standard flow rate of 300 m3⋅h−1, the ratio between the overall reaction volume and the length of the membrane was varied, substantially by varying the volume of reservoir, from and to which circulation of gaseous stream took place. Photomineralization of methane in aqueous solutions was also studied, in the same annular reactor and in the same conditions, but in a concentration range of 0.8–2.0 ppm of C, and by using stoichiometric hydrogen peroxide as an oxygen donor. A kinetic model was employed, from which, by a set of differential equations, four final optimised parameters, k1 and K1, k2 and K2, were calculated, which is able to fit the whole kinetic profile adequately. The influence of irradiance on k1 and k2, as well as of flow rate on K1 and K2, is rationalized. The influence of reactor geometry on k values is discussed in view of standardization procedures of photocatalytic experiments. Modeling of quantum yields, as a function of substrate concentration and irradiance, as well as of concentration of photopromoter, was carried out very satisfactorily. Kinetics of hydroxyl radicals reacting between themselves, leading to hydrogen peroxide, other than with substrate or intermediates leading to mineralization, were considered, and it is paralleled by a second competition kinetics involving superoxide radical anion.